Are Impostors playful? Testing the association of adult playfulness with the Impostor Phenomenon. (1st October 2017) - Brauer, Kay; Proyer, René T.
Abstract: We extend the study of antecedents to the Impostor Phenomenon (IP) by examining associations with adult playfulness. Previous studies showed that playfulness is associated with positive psychological functioning (e.g., healthy coping strategies) and may serve as a protective factor to IP experiences. Aside from a global measure of adult playfulness (in the sense of an easy onset and high intensity of playful experiences along with the frequent display of playful activities) we also tested the association of the IP with four facets of playfulness; namely, Other-directed, Lighthearted, Intellectual, and Whimsical (OLIW). Correlational and regression analyses in two independent samples of students ( N  = 244) and working professionals ( N  = 222) have shown differential association patterns of the OLIW facets towards the IP while the unidimensional conceptualization of playfulness existed independently from the IP. In line with earlier research, the students demonstrated greater levels of IP than the working professionals and also correlational patterns differed. Theoretical and practical implications are discussed. Highlights: Testing associations of the Impostor Phenomenon with facets of adult playfulness Analyses were based on samples of students and working professionals. Lighthearted playfulness robustly predicts the Impostor Phenomenon. Differential effects of Other-directed and Whimsical playfulness across samples